Bosnia and Herzegovina : Policy Notes for the BH Governments - World Bank (Washington, DC, 2013)
Bosnia and Herzegovina (BH) has made substantial progress in economic reconstruction since the end of the war, but much more remains to be done to establish conditions for sustainable private sector-led growth, curtail risks to hard-won fiscal stability, and create an efficient government. The high level of government spending remains supported by a larger than optimal tax burden, primarily reflecting onerous social security contributions, bankruptcy or liquidation. The operational independence of the privatization agencies should be ensured, and transparent methods must be used for divestiture. This paper also notes that deteriorating rural infrastructure, including roads, electricity, village water supply, and irrigation, all constrain rural development. Recommendations are proposed for improving conditions in the agriculture, health, transport, and education sectors.